Noninvasive Local Impedance Determination in Polymer Electrolyte Fuel Cells Stacks - Arnaud Schuller; Thomas J. Schmidt; Jens Eller (ECS Meeting Abstracts, 2023)
Water management in polymer electrolyte fuel cells (PEFC) needs to ensure a homogeneous membrane humidification without local dryout or flooding from inlet to outlet of cell with active areas of some hundreds of square centimeters. Measurement methods that are able to provide spatial resolved information on the current density, membrane conductivity or water content distributions of PEFCs are usually invasive and therefore difficult to use in actual applications. Based on the learnings of the development of electrical impedance tomography (EIT) for PEFCs [1], a new method is presented that is capable to determine 1D humidity profiles between the gas inlet and outlet in a 6-cell commercial stack [2,3]. Local AC current injections and voltage measurements are performed using electrodes positioned all around the fuel cell attached to the flow field plates (see Figure 1a). Each electrode combination characterizes a specific area of the cell as the current crosses the membrane electrode assembly (MEA) very locally. The presentation will discuss the calibration of the local impedance values, the sensitivity of the approach to relative humidity (rH) gradients in the cell (see Figure 1b) and present use cases of measurements during fuel cell operation. Finally, we will present results on multiply frequency AC stimulation that allows local electrochemical impedance measurements and thereby insights beyond membrane conductivity, i.e. into mass transport limitations due to water accumulations in the cell. References [1] A.Schuller, et al., J. Electrochem. Soc. 2022, 169, 044525. DOI: 10.1149/1945-7111/ac6390 [2] A.Schuller, et al., J. Electrochem. Soc. 2022, 169, 074504. DOI: 10.1149/1945-7111/ac7a62 [3] A.Schuller, et al., J. Electrochem. Soc. 2022, 169, 124512. DOI: 10.1149/1945-7111/aca03a Figure 1: a) Scheme of simplified PEFC geometry with electrodes locations at the flow field’s outer surface that are used for current injection (black arrows) and potential measurements (gray arrows) in varying combinations during data acquisition; b) Determined distribution of the cells high frequency resistance for different stack operating conditions (temperature 70°C, RH inlet & outlet 50%). Figure 1